The Use of Game-Based Learning to Improve Students’ Vocabulary Mastery in SMP Barumun 1 Padang Lawas - Ripai Rangkuty, Ahmad; Adena Hasibuan, Lijah (Jurnal Pendidikan Tambusai, 2026)
Vocabulary mastery is a fundamental component of English language learning, yet many junior high school students experience difficulties due to monotonous teaching methods. This study aims to investigate the effectiveness of Word Guessing Game in improving students’ vocabulary mastery and to explore students’ responses toward the use of games in English learning. The research employed a mixed-method approach with a quasi-experimental design. The participants were eighth-grade students of SMP Barumun, consisting of 32 students. Quantitative data were collected through pre-test and post-test, while qualitative data were obtained through questionnaires and classroom observations. The quantitative data were analyzed using descriptive statistics and paired-sample t-test, while qualitative data were analyzed thematically. The findings indicate a significant improvement in students’ vocabulary mastery after the implementation of Word Guessing Game. The results also show that students responded positively, demonstrating higher motivation, engagement, and active participation during the learning process. These findings suggest that Word Guessing Game is an effective and practical strategy to enhance vocabulary learning at the junior high school level.